2020
DOI: 10.1051/matecconf/202032103005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of microstructure on mechanical properties of SLM 3D printed Ti-6Al-4V

Abstract: This research focuses on establishing the relationship between the SLM process parameters, microstructure and mechanical properties in 3D printed ti-6Al-4V. To this end modelling of the thermal history, reflecting the applied process parameters, is linked to the as-printed microstructure, which, in turn, is linked to experimentally determined mechanical properties. The very high cooling rates in the centre of the specimen, as predicted by modelling, lead to a fine, martensitic microstructure, while the slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These results are used in the RVE simulations presented in Section 3.3. More details on the microstructure of Ti-6Al-4V and 316L can be found in [30] and [33], respectively. For both materials, light optical microscopy (LOM) was conducted on an Olympus GX41, revealing elongated columnar grains parallel to the building direction, as shown in Figure 2a and c.…”
Section: Microstructure Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are used in the RVE simulations presented in Section 3.3. More details on the microstructure of Ti-6Al-4V and 316L can be found in [30] and [33], respectively. For both materials, light optical microscopy (LOM) was conducted on an Olympus GX41, revealing elongated columnar grains parallel to the building direction, as shown in Figure 2a and c.…”
Section: Microstructure Characterisationmentioning
confidence: 99%
“…Due to the high cooling rates of the LPBF process, as-built Ti-6Al-4V typically exhibits a purely martensitic α HCP microstructure [33,38], while 316L displays elongated austenite grains with FCC crystal structure [30,39]. Therefore, a single phase material model is assumed for both of the materials, based on the performed X-ray measurements and in…”
Section: Constitutive Model Parameters On the Single Crystal Levelmentioning
confidence: 99%
“…The energy density calculated was 230.8 J/mm 3 . Part of the 3D printed samples was also heat treated at 800 • C for 1 h under the protective atmosphere of argon, then cooled to 500 • C in the furnace, followed by air cooling to obtain optimal mechanical properties as suggested previously [19,20,23]. In addition, a part of the samples for tests was extracted from the milling disc by CAD/CAM milling.…”
Section: Samplesmentioning
confidence: 99%
“…These alloys can be produced in a variety of ways, including by casting, forging, through the wrought process and using various additive manufacturing techniques. Thermal and thermomechanical treatments are applied either as part of the production process or following production, primarily in order to improve the mechanical properties of the end product [19,20]. These processes lead to differing microstructures; in the case of production by casting, for example, the microstructure is lamellar, forging with post-solution heat-treatment results in an equiaxed microstructure, and selective laser melting (SLM), one of the most commonly used additive manufacturing techniques, leads to a martensitic microstructure as a result of the fast cooling rates [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently observed that samples' orientation with respect to the building platform has a strong impact on the mechanical properties as well as on microstructure and surface texture [2,[4][5][6]9,24,28,32]. Concerning the tensile tests, both vertical and 45 • printing directions show slightly higher mechanical properties compared to the horizontal samples in terms of Tensile Strength (TS), Yield Strength (YS), and Elongation (E%) [5,16,24,32].…”
Section: Introductionmentioning
confidence: 99%